Fungal Pathogens Responsible for Diseases in Carrot (Daucus carota L.) Production in Ondo State Nigeria - Adeoye, Omolara Ojuolape (Journal of Science, Technology and Innovation Research, 2026)
Carrot (Daucus carota L.) is a vegetable that is mostly eaten raw without cooking. As a result, it can serve as a vehicle for fungi to move from farm to stomach, while these microflora also contribute to carrot spoilage and postharvest losses. This study, investigated fungi responsible diseases and spoilage of carrots. Carrots were purchased from local farmers in Akure, Ondo State, Nigeria, labeled appropriately and taken to the laboratory for analysis. The carrots were divided into 2 groups (A and B). Group A was further subdivided and stored under refrigeration (4 ± 2 oC) and colanders (30 ± 2 oC) to study fungi associated with spoilage, while group B was used to determine fungi present on fresh carrot surfaces. Eight fungi were isolated from carrot surfaces obtained from four markets (Sacharomyces cerevisiae, Aspergillus nidulas, Pleurothecium recurvatum, Mucus mucedo, Penicillium italicum, Peacilomyces viriotie, Aspergillus niger and Rhizopus nigricans). From spoilt carrots, Sclerotini sclerotiorum, Penicillium natatum, Aspergillus niger, Aspergillus flavus, Mucur mucedo and Rhizopus nigricans were isolated. All these spoilage organisms were implicated in carrot spoilage except A. flavus. Some of the fungi isolated (A. niger and A. flavus) are pathogenic and capable of producing toxic metabolites posing potential health risks to consumers. In addition, Sclerotini sclerotiorum causes devastating economic losses to farmers. Identifying and controlling fungal diseases of carrot is essential for reducing postharvest losses, ensuring food safety, and maintaining the availability of high-quality, nutritious vegetables.